Combining radiotherapy and focused ultrasound for pain palliation of cancer induced bone pain; a stage I/IIa study according to the IDEAL framework - Marcia M.T.J. Bartels; Inez M. Verpalen; Cyril J. Ferrer; Derk J. Slotman; Erik C.J. Phernambucq; Joost J.C. Verhoeff; Wietse S.C. Eppinga; Manon N.G.J.A. Braat; Rolf D. van den Hoed; Miranda van 't Veer-Ten Kate; Erwin de Boer; Harry R. Naber; et al. (Clinical and Translational Radiation Oncology, 2021)
Background: Cancer induced bone pain (CIBP) strongly interferes with patient’s quality of life. Currently, the standard of care includes external beam radiotherapy (EBRT), resulting in pain relief in approximately 60% of patients. Magnetic Resonance guided High Intensity Focused Ultrasound (MR-HIFU) is a promising treatment modality for CIBP. Methods: A single arm, R-IDEAL stage I/IIa study was conducted. Patients presenting at the department of radiation oncology with symptomatic bone metastases in the appendicular skeleton, as well as in the sacrum and sternum were eligible for inclusion. All participants underwent EBRT, followed by MR-HIFU within 4 days. Safety and feasibility were assessed, and pain scores were monitored for 4 weeks after completing the combined treatment. Results: Six patients were enrolled. Median age was 67 years, median lesion diameter was 56,5 mm. In all patients it was logistically possible to plan and perform the MR-HIFU treatment within 4 days after EBRT. All patients tolerated the combined procedure well. Pain response was reported by 5 out of 6 patients at 7 days after completion of the combined treatment, and stabilized on 60% at 4 weeks follow up. No treatment related serious adverse events occurred. Conclusion: This is the first study to combine EBRT with MR-HIFU. Our results show that combined EBRT and MR-HIFU in first-line treatment of CIBP is safe and feasible, and is well tolerated by patients. Superiority over standard EBRT, in terms of (time to) pain relief and quality of life need to be evaluated in comparative (randomized) study.